The logic of violence: an ethnography of Dublin's illegal drug trade - Marsh, Brendan (Routledge advances in ethnography, 2020)
Foreword / by Shadd Maruna -- Introduction -- Order from chaos -- Addiction, violence, and the street -- Debts, deaths, and more debts -- Violent transactions -- Dominance and desistance -- Conclusion: the logic of violence.